«Невидимая гипербола» у Н. В. Гоголя: К вопросу о механизмах дискурсивного выделения - Zel'dovič, Gennadij (Wiener Slawistischer Almanach, 2022)
The author seeks to show that along with obvious, immediately detectable manifestations of Gogol’s famous hyperbolism, there are also instances that can only be identified by careful analysis. These latter instances are special in that the relevant portions of Gogol’s texts display certain features prototypical of another kind of language, i. e. of foreground in narrative discourse, or foreground in lyrical poem (assuming that what is foregrounded here is the part of the poem where the lyrical hero, based on her/his previous experience, discovers an important general truth or fundamentally changes her/his attitude towards oneself or the world). While such a hyperbolism is deeply implicit, relevant fragments are usually felt to be discourse privileged to a greater or lesser degree, which entitles us to view it as a foregrounding marker and suggests some broader conclusions about implicit mechanisms of inner hierarchization of discourse.